Fitness, Function, and Exercise Training Responses after Limb Salvage With a Lower Limb Megaprosthesis: A Systematic Review. Issue 5 (7th March 2019) - Wilson, Paula J.; Steadman, Peter; Beckman, Emma M.; Connick, Mark J.; Carty, Christopher P.; Tweedy, Sean M.
Abstract : Objective: To describe the fitness, function, and exercise training responses of patients following reconstruction of the lower limb with a total femoral (TF), proximal femoral (PF), distal femoral (DF), or proximal tibial (PT) megaprosthesis. Type: Systematic review. Literature Survey: Five research databases were searched systematically for original studies published in English from 2006 to 2017 that reported fitness, functioning, or exercise training responses for one or more of the four types of lower limb megaprosthesis listed above. Methodology: Methodologic quality was assessed using a 22‐item modified STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) checklist. Synthesis: Of the 5342 articles retrieved, 28 met the inclusion criteria. Thirteen studies reported fitness outcomes, primarily in PT, with none in TF. Impaired knee extensor strength of the affected limb was reported following limb salvage with PF, DF, and PT megaprosthetics. Impaired flexibility was reported following limb salvage with DF and PT megaprosthetics. Functional outcomes were described in all studies and were most commonly reported using the Musculoskeletal Tumor Society (MSTS) system score. Results indicated no clear difference in functional outcomes between megaprosthesis locations. No studies evaluated exercise training responses. Conclusions: This review identified impairments of lower limb strength and flexibility following limb salvage with a lower limb megaprosthesis. Similarity in functional outcomes for all four reported megaprosthetic locations may indicate a lack of sensitivity in outcome measures, including the absence of items assessing higher‐level functioning. Exercise interventions that aim to improve fitness and function in this population have not been evaluated but are required given increasing 5‐year survival rates. Level of Evidence: I